Extremely efficient flexible organic solar cells with a graphene transparent anode: Dependence on number of layers and doping of graphene. (January 2021) - Du, Jinhong; Zhang, Dingdong; Wang, Xiao; Jin, Hui; Zhang, Weimin; Tong, Bo; Liu, Yu; Burn, Paul L.; Cheng, Hui-Ming; Ren, Wencai
Abstract: Graphene has shown tremendous potential as a transparent conductive electrode (TCE) for flexible organic solar cells (OSCs). However, the trade-off between electrical conductance and transparency as well as surface roughness of the graphene TCE with increasing layer number limits power conversion efficiency (PCE) enhancement and its use for large-area OSCs. Here, we use a 300 nm-thick poly[(2, 5-bis(2-hexyldecyloxy)phenylene)- alt -(5, 6-difluoro-4, 7-di(thiophen-2-yl)benzo[ c ]-[1, 2, 5]thiadiazole)]:[6, 6]-phenyl-C71 -butyric acid methyl ester blend as the photoactive layer and a benzimidazole (BI)-doped graphene as the transparent anode to demonstrate efficient OSCs with good flexibility. It is found that 3 layer (L) graphene had the best balance between sheet resistance, optical transmittance and surface roughness for optimized cell design. A 0.2 cm 2 cell with a 3L BI-doped graphene anode had a PCE of 6.85%, which is one of the highest PCE values reported so far for flexible graphene anode-based OSCs. The flexible cells were mechanically robust, showing only a small performance degradation during up to 250 flexing cycles. Moreover, the combination of the thick photoactive layer with the optimized 3L BI-doped graphene TCE enabled production of 1.6 cm 2 flexible OSCs with a PCE of 1.8%. Our work illustrates the importance of graphene TCE development for flexible OSCs as well as other wearable optoelectronic devices. Graphical abstract: Image 1 Highlights: Extremely efficient flexible organic solar cells with a doped graphene transparent anode are demonstrated. 3 layer graphene is determined to be optimal for the cell design. A 0.2 cm 2 cell achieves a high power conversion efficiency of 6.85%. The thick photoactive layer enables production of a 1.6 cm 2 -large flexible cell with graphene anode.